2020
DOI: 10.1088/1741-2552/ab9843
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the orientation selectivity in V1 and V4 of macaques by quadratic phase coupling

Abstract: Objective. Orientation selectivity is one of the significant characteristics of neurons in the primary visual cortex (V1). Some neurons in extrastriate visual cortical areas also exhibit certain orientation selectivity. But it is still not well understood that how the orientation selectivity generates. Most previous studies about the orientation selectivity are based on the spike firing rate. However, the spikes are prone to be biased by the detection and sorting algorithms. Then, in this paper, the local fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Its application spans across multiple fields, including neuroscience, engineering, biology, and signal processing, where understanding nonlinear behaviors is crucial for making meaningful interpretations and improving modeling techniques. QPC can reveal how different brain regions or neurons interact nonlinearly during various cognitive tasks or in different brain states and thus can contribute for advancing our knowledge of brain functional connectivity, as shown in evoked potentials and EEG recordings [40][41][42][43][44] , local field potentials [45][46][47] , and magnetoencephalography 46,48 . The current study has introduced a straightforward interaction network model, exemplified by a noisy instantaneous multiplier showcasing characteristic QPC, specific to…”
Section: Discussionmentioning
confidence: 99%
“…Its application spans across multiple fields, including neuroscience, engineering, biology, and signal processing, where understanding nonlinear behaviors is crucial for making meaningful interpretations and improving modeling techniques. QPC can reveal how different brain regions or neurons interact nonlinearly during various cognitive tasks or in different brain states and thus can contribute for advancing our knowledge of brain functional connectivity, as shown in evoked potentials and EEG recordings [40][41][42][43][44] , local field potentials [45][46][47] , and magnetoencephalography 46,48 . The current study has introduced a straightforward interaction network model, exemplified by a noisy instantaneous multiplier showcasing characteristic QPC, specific to…”
Section: Discussionmentioning
confidence: 99%
“…Its application spans across multiple fields, including neuroscience, engineering, biology, and signal processing, where understanding nonlinear behaviors is crucial for making meaningful interpretations and improving modeling techniques. QPC can reveal how different brain regions or neurons interact nonlinearly during various cognitive tasks or in different brain states and thus can contribute for advancing our knowledge of brain functional connectivity, as shown in evoked potentials and EEG recordings [24][25][26][27][28] , local field potentials [29][30][31] , and magnetoencephalography 30,32 . The current study has introduced a straightforward interaction network model, exemplified by a noisy instantaneous multiplier showcasing characteristic QPC.…”
Section: Discussionmentioning
confidence: 99%
“…Alpha (8-12 Hz) rhythms in the human brain were first observed in 1928 [7]. Other characteristic brain activities have also been successively investigated, including the delta (0.5-4 Hz), theta (4-8 Hz), beta (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and gamma (above 30 Hz) frequency bands [8][9][10]. Moreover, it was found that the neural oscillations in different frequency bands interact mutually, which is called cross-frequency coupling (CFC) in the literature [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was found that the neural oscillations in different frequency bands interact mutually, which is called cross-frequency coupling (CFC) in the literature [11][12][13]. Several theoretical analyses and experimental findings have demonstrated that CFC is fundamental for neural communication and encoding, which bridges the gap between neural oscillations and brain functions [14][15][16][17][18][19][20]. Additionally, it has been proven that CFC is a pathological pattern in various conditions correlating with symptom severity [21][22][23].…”
Section: Introductionmentioning
confidence: 99%